2021
DOI: 10.3389/fmicb.2021.716761
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Probiotic Limosilactobacillus reuteri KUB-AC5 Against Salmonella Infection in a Mouse Colitis Model

Abstract: Acute non-typhoidal salmonellosis (NTS) caused by Salmonella enterica Typhimurium (STM) is among the most prevalent of foodborne diseases. A global rising of antibiotic resistance strains of STM raises an urgent need for alternative methods to control this important pathogen. Major human food animals which harbor STM in their gut are cattle, swine, and poultry. Previous studies showed that the probiotic Limosilactobacillus (Lactobacillus) reuteri KUB-AC5 (AC5) exhibited anti-Salmonella activities in chicken by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…In this study, IL-1β and TNF-α concentrations were linearly diminished, whereas IL-10 concentration was linearly augmented with the increasing doses of LM1 supplementation in the diet. Analogous results of reduced serum concentrations of IL-1β, IL-6, and TNF-α have been reported in rats with mild inflammation who were fed on a mixed Limosilactobacillus fermentum diet and as well as in lipopolysaccharide-challenged weaning pigs whose diets were supplemented with L. salivarius and L. mucosae AN1 ( 9 , 10 , 34 , 35 ). Low et al ( 36 ) have reported that IL-1β responds to microbial invasion as well as tissue damages and rapidly stimulates immune responses by activating lymphocytes or inducing the release of other cytokines.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, IL-1β and TNF-α concentrations were linearly diminished, whereas IL-10 concentration was linearly augmented with the increasing doses of LM1 supplementation in the diet. Analogous results of reduced serum concentrations of IL-1β, IL-6, and TNF-α have been reported in rats with mild inflammation who were fed on a mixed Limosilactobacillus fermentum diet and as well as in lipopolysaccharide-challenged weaning pigs whose diets were supplemented with L. salivarius and L. mucosae AN1 ( 9 , 10 , 34 , 35 ). Low et al ( 36 ) have reported that IL-1β responds to microbial invasion as well as tissue damages and rapidly stimulates immune responses by activating lymphocytes or inducing the release of other cytokines.…”
Section: Discussionsupporting
confidence: 68%
“…[91] There is also a very broad assortment of biological agents that are used in an analogous manner that include E. coli, B. vulgatus, salmonella, and others. [92,93] These studies focus heavily upon adaptive (typically aspects of T-cell immunobiology) and innate immune cell functional relationships.…”
Section: The Use Of Acetic Acid To Induce Colitismentioning
confidence: 99%
“… The criteria for mouse cecal histopathological scoring used in this study ( Buddhasiri et al, 2021 ). …”
Section: Supplementary Materialsmentioning
confidence: 99%